2005
DOI: 10.1112/s0024609305004418
|View full text |Cite
|
Sign up to set email alerts
|

Description of All Complex Geodesics in the Symmetrized Bidisc

Abstract: Effective formulae are found for the complex geodesics in the symmetrized bidisc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…[2,3,4], [7], [16]). Description of automorphisms in G 2 was given in [12], description of proper mappings in G 2 was given in [9].…”
Section: Introductionmentioning
confidence: 99%
“…[2,3,4], [7], [16]). Description of automorphisms in G 2 was given in [12], description of proper mappings in G 2 was given in [9].…”
Section: Introductionmentioning
confidence: 99%
“…Note that the symmetrized bidisc is (1, 2)-circular. The uniqueness result on geodesics and their complete description in G 2 are given in [16] and [5]. Here, we show how one can use our results to give a simpler proof of the description of all geodesics in G 2 passing through the origin.…”
Section: Reinhardt Domains Recal That a Domainmentioning
confidence: 75%
“…The symmetrized bidisc and its higher dimensional analogue, the symmetrized polydisc G n , has been recently extensively studied (see e.g. [3], [4], [7], [16], [11], [5] and others). It was shown that G 2 cannot be exhausted by domains biholomorphic to convex ones (see [7], [10]).…”
Section: Letmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently studied by many authors, e.g. [1], [2], [4], [8]. The domain G 2 is the first known bounded pseudoconvex domain for which the Carathéodory and Lempert functions coincide, but which cannot be exhausted by domains biholomorphic to convex domains; cf.…”
mentioning
confidence: 99%